Relación entre el estrés laboral y el engagement en trabajadores de sectores públicos y privados - Mosquera Basas, Maria Pia (2021)
Stress is a psychological variable present in everyone lives to a greater or lesser extent, however, when it manifests itself negatively is when it generates a harmful impact on the individual, which can have repercussions in various aspects, one of them being work engagement or commitment. The objective of this study is to identify the relationship between stress and engagement in public and private sector workers, thorugh the collection and exploration of empirical evidence. In order to do this, a systematic research was carried out, on several data base and following the guidelines of the PRISMA guide (Urrútia & Bonfill, 2010), a series of exclusion and inclusion criteria were applied, after which 7 scientific articles that responded to the objective of the report, were selected. After the analysis of the selected investigations, it was evidenced that 6 out of 7 confirmed a negative correlation between stress and engagement in workers. However, the article that rejected the hypothesis allowed to visualize the need to deepen in future research the relationship of both variables in different contexts and populations. Therefore, it is concluded that higher stress levels on workers, means lower levels of engagement